Analisis Kemampuan Membaca Permulaan Pada Siswa Kelas I MI Mahir Ar Riyadl Surabaya - Indra, M Fadhil; Saputra, Andra; Haq, Chairul (Universitas Trunojoyo Madura, 2024)
This research aims to determine the influence of visual design on students' interest in learning in elementary schools, especially on the use of colors and shapes in learning materials. Attractive visual designs are believed to increase students' interest and understanding, which in turn can improve their learning outcomes. This research used an experimental design with two groups, namely the experimental class which received visual design treatment and the control class which used conventional learning materials. Data was collected through pretests and posttests given before and after treatment. The results showed that there were significant differences between the experimental class and the control class. In the pretest, the average score of the experimental class was 3.26 points higher with a value of t = 2.584 and p = 0.013, while in the posttest, the difference in the average score increased to 11.12 points with a value of t = 4.215 and p = 0.000. These findings indicate that the use of attractive visual design can improve student learning outcomes, especially in material presented with visual elements such as color and shape. This research supports theories which state that good visual design can increase students' motivation, interest and understanding in the learning process.